Effects of torrefaction and organic-acid leaching pretreatment on the pyrolysis behavior of rice husk. (15th April 2018) - Zhang, Shuping; Su, Yinhai; Xu, Dan; Zhu, Shuguang; Zhang, Houlei; Liu, Xinzhi
Abstract: In this study, torrefaction and organic-acid leaching pretreatment of rice husk samples was performed and their effects on the pyrolysis behavior were evaluated by TGA and laboratory scale pyrolysis reactor. The fuel characteristics of rice husk samples after pretreatment were improved. The results of ICP-OES analysis indicated that torrefaction process increased most inorganic species concentrations except Cl in the torrefied rice husk sample. Meanwhile, torrefaction decreased the removal efficiencies of inorganic species during leaching process. As the results of TGA shown, torrefaction and leaching pretreatment significantly changed the pyrolysis behavior. For laboratory scale pyrolysis experiment, the results indicated that torrefaction process reduced the bio-oil yield with the increase of the yield of char, but leaching process followed by torrefaction alleviated the adverse effects of torrefaction process. For the rice husk sample after combined torrefaction and leaching process the chemical compounds of phenols and sugars in bio-oil were enriched. Furthermore, the chemical compounds distribution in bio-oil after combined torrefaction and leaching pretreatment process was concentrated in the range between C6 and C9, which was conducive to refining gasoline by upgrading. Combined torrefaction and leaching process has the promoting role on the quality of bio-oil according to the physical properties of bio-oil. Highlights: Torrefaction and organic-acid leaching pretreatment of rice husk was performed. Torrefaction and leaching pretreatment significantly changed pyrolysis behavior. Leaching followed by torrefaction alleviated the adverse effects of torrefaction. Combined pretreatment process has the role on improvement of bio-oil quality.